Magnetic Drug Delivery: Where the Field Is Going - Price, Paige M.; Mahmoud, Waleed E.; Al-Ghamdi, Ahmed A.; Bronstein, Lyudmila M. (Frontiers in Chemistry, 2018)
Targeted delivery of anticancer drugs is considered to be one of the pillars of cancer treatment as it could allow for a better treatment efficiency and less adverse effects. A promising drug delivery approach is magnetic drug targeting which can be realized if a drug delivery vehicle possesses a strong magnetic moment. Here, we discuss different types of magnetic nanomaterials which can be used as magnetic drug delivery vehicles, approaches to magnetic targeted delivery as well as promising strategies for the enhancement of the imaging-guided delivery and the therapeutic action.